Impact of Grain Production on Agricultural Carbon Emission in Jharkhand, India: An Empirical Analysis - Bara, A.; Lal, A. K.; Singh, U. (Journal of Scientific Research, 2025)
This study intends to determine the inter-relationship among carbon emissions and economic development from agriculture in Jharkhand, during 2005-2022, utilizing decoupling and decomposition analysis. The decoupling analysis revealed a weakly decoupled state for 7 years, followed by strongly decoupled and strongly coupled states for 3 years, an expansively coupled state for 2 years, a weakly coupled state for one year, and a recessively decoupled state for one year. This suggests that there was no consistent evolutionary path from the coupled state to the decoupled state. However, the empirical findings of the Log Mean Divisia Index method suggest that the rise in agricultural carbon emissions from 2005 to 2022 is primarily due to the effects of agricultural economics followed by the agricultural labor force. Additionally, factors such as the intensity of agricultural carbon emissions and agricultural structure tend to decrease agricultural carbon emissions, with the intensity of emissions having the largest impact on reducing emissions. Furthermore, the combination of decoupling and decomposition analysis suggests that the environmental pressure declined with a rise in the agricultural economy in 2008, 2009, and 2018. The intensity of agricultural carbon emissions significantly contributed to reducing overall emissions during these years. Overall, efforts to reduce carbon emissions from the agricultural sector in Jharkhand are still ineffective.